The Influence of Total Assets and Total Debt on Net Profit at PT Darya Varia Laboratoria Tbk for the Period 2016-2023 - Ningsih, Putri Dewi Fitria; Moch, Rully; Ichsan, Ichsan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was conducted to determine the effect of total assets and total debts on net income. The object of this research was carried out at PT Darrya Varria Labboratoria Terbka, with secondary data types taken from the financial statements for 8 years from 2016-2023. The type of research used is quantitative research with an associative descriptive method. The population in this study is the financial statements for 2016-2023. The sampling technique in this study uses Non-probability Sampling. While the data analysis used is the classical assumption test which includes the data normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, correlation test, determination coefficient test and multiple linear regression, partial and simultaneous hypothesis test. Based on the results of the analysis that has been carried out, it shows that the correlation value of total assets to net income is 0.166 which is included in the very weak category, and the correlation value of total debt to net income is 0.038 which is included in the weak category. Based on the determination analysis that has been carried out, it shows that the amount of contribution from the influence of the dependent variable (Net Income) is 0.071% and the remaining 3.30% is explained by other variables that are not studied